Study on genotype x environment interaction of yield in sesame (sesamum indicum l.) - Hussien Mohammed, Zenebe Mekonnen (Journal of Phytology, 2009)
Seed yield stability of twenty sesame genotypes of different sources of origin were studied for GEI in randomized complete block design with three replications across six environments in 2006. The objectives were to estimate the nature and magnitude of GEI for seed yield, and to identify stable sesame genotypes for general adaptation, Combined analysis of variance showed highly significant (p<0.01) difference for the main and interaction effect for the trait studied, suggesting differential response of genotypes across testing locations and the need for stability analysis. Genotypes Tatte, Mehado-80, E, and S gave high mean seed yield of 559.2, 432.0, 363.6 and 348.3 kg/ha, respectively. The lowest seed yield of 170.1 kg/ha was obtained from genotype Abasena. AMMI stability analysis methods were used to further shed light on the GEI of seed yiel. Two IPCA of AMMI were significant (P<0.01) and captured the largest portion of variation of the total GEI for the trait studied, which indicated that the AMMI model 2 was the best for the data set. Genotypes Temax (1), Acc 051 02 sel 6 (7), Clusu 5 (13), Kelafo 74 (20), NN 0136 sel 2 (6), Acc 212 332 4 (8), Addi (9), and Acc 051 02 sel 10 (11) were the only genotypes showed relatively little GxE interaction in terms of both IPCA1 and IPCA2 axes and therefore stable. The high-yielding genotypes Tatte, Mehado-80 and E were unstable and specifically adapted to high-yielding environments (Goffa, Arbaminch, and Derashie).